Understanding fintech continuance: perspectives from self-efficacy and ECT-IS theories. Issue 9 (21st July 2020) - Shiau, Wen-Lung; Yuan, Ye; Pu, Xiaodie; Ray, Soumya; Chen, Charlie C.
Abstract : Purpose: The purpose of this study is to clarify theory and identify factors that could explain the level of fintech continuance intentions with an expectation confirmation model that integrates self-efficacy theory. Design/methodology/approach: With data collected from 753 fintech users, this study applies partial least square structural equation modeling to compare and select the research model with the most predictive power. Findings: The results show that financial self-efficacy, technological self-efficacy and confirmation positively affect perceived usefulness. Among these factors, financial self-efficacy and technological self-efficacy have both direct and indirect effects through confirmation on perceived usefulness. Perceived usefulness and confirmation are positively related to satisfaction. Finally, perceived usefulness and satisfaction positively influence fintech continuance intentions. Originality/value: To the best of our knowledge, this is one of the earliest studies that investigates the effect of domain-specific self-efficacy on fintech continuance intentions, which enriches the existing research on fintech and deepens our understanding of users' fintech continuance intentions. We distinguish between financial self-efficacy and technological self-efficacy and specify the relationship between self-efficacy and continuance intentions. Moreover, this study highlights the importance of assessing a model's predictive power using the PLSpredict technique and provides a reference for model selection.